Effect of Fermented Feeds on Weaned Piglets Experimentally Infected with Escherichia coli - Karaye, Gloria Pisha; Ola-Fadunsin, Shola David; Tanko, Polycarp Nwunuji; Kudi, Caleb Ayuba (Media Kedokteran Hewan, 2024)
Sixty large white breed piglets aged between 28 and 35 days were randomly assigned to five replicate groups (Bu1, Bu2, Bd1, Bd2, Bs1, Bs2, Lc1, Lc2, C1, and C2) with six pigs per group. The Bu1 and Bu2 groups were fed with wet and dry basal diets, respectively, supplemented with 0.8 mL (6 x 106 colony-forming units (CFU)) of Lactobacillus isolated from burukutu (beverage made from sorghum grains). The Pg1 and Pg2 groups were fed with wet and dry basal diets, respectively, supplemented with 0.8 mL (6 x 106 CFU/mL) of Lactobacillus isolated from pig hindguts. The Bs1 and Bs2 groups were fed with wet and dry basal diets supplemented with 0.8 mL (6 x 106 CFU/mL) of Bacillus subtilis and Bacillus pumilus, respectively. The Lc1 and Lc2 groups were fed with wet and dry basal diets supplemented with 0.8 mL (6 x 106 CFU/mL) of Lactobacillus acidophilus, respectively. Meanwhile, the C1 and C2 groups as the control groups were fed with wet and dry basal diets, respectively. The treatment and control animals were infected with Escherichia coli at 6 mL (1 x 1010 CFU/mL) orally. Aseptically collected fecal samples from the piglets in each group showed significant bacteriological and pathological differences. This study suggested that Lactobacillus species isolated from burukutu, pig hindguts, and industrial probiotics could inhibit colibacillosis.